Manipulating the Trade‐off Between Quantum Yield and Electrical Conductivity for High‐Brightness Quasi‐2D Perovskite Light‐Emitting Diodes. (9th October 2018) - Wang, Zhibin; Wang, Fuzhi; Sun, Wenda; Ni, Ruihao; Hu, Siqian; Liu, Jiyan; Zhang, Bing; Alsaed, Ahmed; Hayat, Tasawar; Tan, Zhan'ao
Abstract: Quasi‐two‐dimensional (quasi‐2D) perovskites are attracting much attention due to their impressive luminescence properties. However, the introduction of insulating bulky cations reduces the charge transport property of mixed‐dimensional perovskites and leads to lowered brightness and increased turn‐on voltage. The trade‐off between high photoluminescence quantum yield (PLQY) and electrical conductivity should be well manipulated to obtain high‐performance perovskite light‐emitting diodes (PeLEDs). Herein, quasi‐2D perovskite BA2 (CsPbBr3 )n‐1 PbBr4 ‐PEO with high PLQY and excellent carrier injection efficiency is demonstrated by incorporating bulky n ‐butylammonium bromide (BABr), CsPbBr3, and polyethylene oxide (PEO). BA can intercalate into the three‐dimensional perovskite framework to form a layered (quasi‐2D) perovskite structure. The ion conductive polymer PEO is used to protect quasi‐2D perovskite crystals. Additional BABr is removed by using anhydrous isopropyl alcohol as a washing agent due to its selective dissolubility. By carefully modulating the optical and electrical properties of quasi‐2D perovskite films, the maximum luminance of PeLEDs is dramatically enhanced from 191 to 33533 cd m −2, which is the brightest green quasi‐2D PeLED reported thus far, leading to an increase in external quantum efficiency from 1.81% to 8.42%. This work provides a promising route to control the optical and electrical properties of quasi‐2D perovskite films for high‐performance optoelectronic devices. Abstract : A quasi‐2D perovskite with high photoluminescence quantum yield and excellent carrier injection efficiency is demonstrated by incorporating n ‐butylammonium bromide, CsPbBr3 and polyethylene oxide. By modulating the optical and electrical properties of quasi‐2D perovskite films, the maximum luminance of PeLEDs is dramatically enhanced from 191 to 33 533 cd m −2, which is the brightest value yet observed for green quasi‐2D PeLEDs.